The health of populations : general theories and particular realities - Kunitz, Stephen J. (Oxford University Press, 2007)
In the maelstrom of current public health debate over the social determinants of health, this book offers a discussion on the roots of prevalent strains of thought on the matter. The author brings an independent perspective to bear on the debate.